PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERBASIS INDUSTRI KREATIF DI KOTA MALANG - Amin Dwi Ananda; Dwi Susilowati (Jurnal Ilmu Ekonomi JIE, 2017)
The goal’s research to knowing the UMKM develop based on creative industry with seeing an strength, weekness, treath, and opportunity in kuliner sector, art, fashion,music, and interactive playing in Malang, and to decide the main strategy to UMKM industry. The type of the research was used is descriptive qualitative.  The result of the research has some sector, it has strength, weekness, treath, opportunity which different. Beside that, there are problems in every sector such as human sourch (SDM) in kuliner, art, fashion, music, and interactive playing. On institution factor include kuliner, art, fashion, music. On infrastructure factor and technology include art and interactive playing. And marketting factor include kuliner sector, art, fashion, music, so it need to make teamworks between industry creative sector with goverment or swasta.Keywords : Creative Industry, Strength, Weekness, and Opportunity, Treath